DHF Prevention Efforts in Sumbersari Jember: Assessment of Aedes aegypti Resistance Status to Deltamethrin - Reni Puspitasari; Hidayatur Rohmah; Husnatun Nihayah; Purwatiningsih; Eva Tyas Utami; Susantin Fajariyah; Asmoro Lelono (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aims to determine the resistance status of Ae. aegypti to the deltametrin insecticide in Sumbersari Jember Village. A total of 100 2nd generation female Ae. aegypti were tested using the CDC bottle bioassay with a deltamethrin dose of 10 μg/ml and a diagnostic time of 30 minutes. Molecular detection using AS-PCR was also performed to detect kdr mutations at position 1016 of the VGSC gene. Mortality data was calculated using Ms.Excel with a confidence level of 95%. The molecular wight of the PCR product is calculated using a gel analyzer application. The results of the CDC bottle bioassay show that the Ae aegypti population is still tolerant to the insecticide deltamethrin (91,25% in mortality rate). However, molecular analysis confirms the presence of a mutation at position 1016 of the voltage-gated sodium channel (VGSC) gene (homozygous mutation), which is known to be the primary target of pyrethroid insecticides. These findings indicate that although phenotypic resistance has not yet fully developed, the mosquito population has shown early indications of target-site insensitivity to deltamethrin, which has the potential to develop into resistance under sustained selection pressure. Further use of deltamethrin insecticide may potentially increase phenotypic resistance, namely a decrease in mosquito mortality after exposure to deltamethrin insecticide. Therefore, an integrated vector control strategy and routine monitoring of mosquito resistance status in the region are required.